POSSIBILIANISM ON THE BASIS OF PHENOMENOLOGY AND PSYCHOLOGY - Rainio, Kullervo (Advances in Social Sciences Research Journal, 2018)
This article is based on Kant’s transcendental idealism and the phenomenological conception of ontology. It specifies the basic concepts needed to describe possibilianism. The basic axiom is: All possible states of affairs exist – either as potentialities or as actualized (become real) in the interpreted world. Only what is logically contradictory is impossible. All processes are assumed to be stochastic. Potential states of affairs are transcendental, we do not have knowledge of them as such (an sich), but a certain probability, p(E), for them of existing as possibilities is assumed. The actualization of a possibility in the interpreted world takes place conditionally, and the probability that this condition is fulfilled is p(C). p(E) multiplied by p(C) indicates the probability for a state of affairs to be actualized (at a given time). Human beings are able, by their acts (choices) to influence p(C), i.e. favorability of the conditions for a state of affairs to become real, and thus guide the actualization of possibilities in the interpreted world in the form of perceived material world or representations or thoughts. Hence, they can function as “co-creators”. Culture plays here a central role. The last chapter examines the impact of possibilianism on science and on human world view. Possibilianism does not refute scientific findings, but it could bring radical changes to the world view based on them.